Towards improving the public service by activating intrapreneurship: A field study of a sample of support and accompaniment in the state of Djelfa - Missaoui, Abdulbaqi; Hazerchi, Tarek; Benmessaoud, Atallah (Dirassat Journal Economic Issue, 2020)
The aim of this study is to address the various theoretical literature dealing with the topics of intrapreneurship and the public service and analysis of the reality of the latter in the Algerian government administrations and the possibility of taking advantage of the dimensions of entrepreneurship to improve the latter. It also relied on the descriptive analytical method and the inductive method to address their problematic, This study found that internal leadership is a modern phenomenon and there is a difficulty in spreading its culture in the public administrations, which necessitates the launching of programs to develop the internal leadership in public administrations. This can only be achieved through the adoption of the senior management of its curricula and strategies.